Ancient Greece in Modern Marseille: Elements of an Urban History (1800–1950) - Tsiambaos, Kostas; Kritikos, Christos-Georgios (Historein, 2023)
Although the Greek origins of Marseille were never questioned, the actual presence of its Greek past was hardly obvious in the image of the city. However, the Greek “memory” of the city had been kept alive throughout the nineteenth and early twentieth centuries. Keeping in mind that a growing number of Greeks had begun to settle in Marseille already during the late eighteenth century, leading to the gradual establishment of a vibrant Greek community, we will question the role of that community in the discourse on the ancient Greek origins of Marseille. The ways both Greeks and French reconstructed the city’s Greek heritage in the most ancient French city can provide further insight into how memory and identity intersect across languages, ideas, origins, expressions, projections and representations connecting France and Greece in modern times.